Grocery Inventory Management System for Kedai Buah-buahan Misri Sumiran - Mohd Hanafi, Nabila Syafiqah; Aman, Hannani (Applied Information Technology And Computer Science, 2025)
This project centres on the imperative need for efficient inventory management within the neighborhood grocery store, Kedai Buah-buahan Misri Sumiran. The proposed Grocery Inventory Management System seeks to address these issues of inaccurate records, overlooked expiration dates, and disorganized supplier details by providing a modernized and streamlined solution. Development of this system utilizes the Waterfall Model methodology as the requirements are all stated clearly in the planning phase. The Grocery Inventory Management System for Kedai Buah-buahan Misri Sumiran involves the development of a web-based system with modules for registration, product management, inventory tracking, supplier management, and reminders for impending expirations and low stocks. Low stock are determined by the stock percentage of each prodcut that reach 20% and below. The stock percentage is calculated by the maximum stock level against the current stock. Anticipated outcomes include increased efficiency in stock management, accurate recording of inventory items, and timely reminders for expiration dates and low stocks. The significance of the project lies in enhancing operational efficiency, minimizing waste, and facilitating informed decision-making for both the store owner and employees. Developing the mobile app version of this web-based system would be the future wish of this project.